Peran Guru Bimbingan Konseling Dalam Menanamkan Nilai Karakter Disiplin Pada Siswa Kelas XI MAN 4 Kebumen - Durotun Nafisah; Mahrur Adam Maulana; Rose Kusumaning Ratri (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine the forms of discipline in MAN 4 Kebumen, to describe and toknow the role of Counseling Guidance teachers in instilling the value of disciplined characterin class XI students of MAN 4 Kebumen. This research is in the form of field research. Thisstudy uses a qualitative approach. The subjects in this study were Counseling Guidanceteachers and students of class XI MAN 4 Kebumen. Data collection methods used areobservation, interviews, and documentation. While the data analysis technique uses datareduction, data presentation, and drawing conclusions. The results of this study can beconcluded that: (1) The forms of student discipline at MAN 4 Kebumen, are a manifestationof the application of the madrasa rules that have been agreed upon and to be obeyed by allstudents of MAN 4 Kebumen (2) The role of counseling guidance teachers in instilling valuesThe character of discipline at MAN 4 Kebumen is that BK teachers play an active role interms of discipline, starting from the example set by the BK teacher to students, then theguidance provided. In addition, BK teachers also provide direction and motivation in instillingthe value of disciplined character in students. Then the BK teacher also gives direct sanctionsto students who have violated the rules of the madrasa and the BK teacher always conductsinspections or routine tours to check student order in learning activities. BK teachers will alsocarry out home visits for students who often do not go to madrasas